Multifunctional NiFe2O4 nanoparticles for sodium-ion batteries, sensing, and photocatalysis. (12th November 2021) - Patil, S. B.; Patil, Shivaraj B.; Deepa, S.; Udayabhanu,; Nagaraju, G.; Swamy, B. E. Kumara
Abstract : NiFe2 O4  NPs synthesized by co-precipitation method exhibited excellent electrochemical properties towards sodium ion batteries and oxidation of uric acid. NiFe2 O4  NPs also exhibited good catalytic activity for simultaneous degradation of multiple dyes. Abstract : NiFe2 O4 nanoparticles (NPs) have attracted great attention in various areas, such as sodium-ion batteries (NaIBs), biosensing, and catalysis. In this direction, herein, NiFe2 O4 NPs were synthesized via a simple co-precipitation method using cetrimide as a surfactant, and they were characterized using different physicochemical techniques. NiFe2 O4 was examined as a negative electrode for NaIBs. The NiFe2 O4 anode exhibited excellent electrochemical and mechanical stability. It delivered a high specific capacity of 1103 mA h g −1 in the first cycle, which is much higher than its theoretical capacity (915 mA h g −1 ), and a capacity of 200 mA h g −1 was achieved at the end of 100 cycles. It exhibited excellent catalytic activity towards the electrochemical oxidation of uric acid (UA), and this was studied in detail based on cyclic voltammograms. In addition to this, the NPs showed good photocatalytic activity under visible light irradiation for the degradation of mixed organic dyes.